(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The relevance of the topic of the digital economy is due to the following factors: The rapid development of digital technologies. Digital technologies are developing at a rapid pace, and they are increasingly penetrating various spheres of society. This leads to the transformation of economic systems and society as a whole. Opportunity to improve production and distribution efficiency. Digital technologies make it possible to increase the efficiency of production and distribution, which leads to lower costs and increased productivity. This contributes to economic growth and improved living standards of the population.